Preserving Child's Faith in Malaysian Law: A Maqasidic Approach - Zanariah Binti Noor; Nazirah Lee (Ulumuna, 2023)
Preserving faith is the most significant goal for Muslims. However, fulfilling these objectives in the best possible way according to the principle of maqāṣid al-sharī’ah(the objective of Islamic law) within the framework of the dual system of Malaysian law is challenging. Preserving faith within maqāṣid al-sharī’ah discussion provides enormous opportunities for Muslims to nurture and protect their Islamic faith while regulating the laws that prohibit any harmful elements that could jeopardize it. The Federal Constitution of Malaysia guarantees everyone's freedom of religion. However, freedom of religion provided under Malaysian law has restrictions due to the uniqueness of Malaysian history. This article critically discusses the maqasidic-approach adopted to preserve Muslim child's faith. This article examines the government's effort to maintain Muslim child's faith concerning the laws and policies of education and Malaysian law on issues linked to the conversion of Muslims to other faiths and vice versa. The court decision on child's religion cases indicates a distinct feature of Muslim and non-Muslims' right to freedom of religion under Malaysian law. There are prospects for utilizing the maqāṣid al-sharī’ah framework effectively to promote the preservation of a child's faith in the context of Malaysian law.